EVALUASI IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) TAHUN 2020 DI DESA PANGIAN KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - NGODU, INDI WIDIA; TULUSAN, FEMMY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to determine the evaluation of the implementation of the PTSL program in Pangian Village, East Passi District, Bolaang Mongondow Regency. This study uses descriptive qualitative research, as for the type of research used in this study is evaluation. Sources of data used in this study are primary data and secondary data with data collection techniques, namely observation, interviews and documentation. The theory used is the theory of William N. Dunn (2003) with six evaluation criteria. Based on the results of the study, it shows that the Evaluation of the Implementation of the Complete Systematic Land Registration Program (PTSL) in 2020 in Pangian Village, East Passi District, Bolaang Mongondow Regency has been carried out well. As for the findings from the research, it is known that the evaluation of the implementation of the PTSL program in Pangian Village is classified as good because it is seen from the six evaluation criteria studied, namely effectiveness, efficiency, adequacy, leveling, responsiveness and accuracy which are considered good. However, in the implementation of this program there are still various obstacles. The suggestions from the researcher are for the BPN implementer and the Village Government to continue to build good coordination, prepare and continue to improve skills in measuring land manually without having to use automatic measuring tools that still require an internet connection, continue to improve socialization on public understanding about the program. PTSL and can prepare plans that attract more attention from the community, and continue to improve performance so that program implementation continues to run effectively and efficiently. Keywords: Evaluation, Implementation, PTSL